Assessing Global, Regional, and National Time Trends and Associated Risk Factors of the Mortality in Ischemic Heart Disease Through Global Burden of Disease 2019 Study: Population-Based Study - Tingting Shu; Ming Tang; Bo He; Xiaozhu Liu; Yu Han; Chang Liu; Pedro A Jose; Hongyong Wang; Qing-Wei Zhang; Chunyu Zeng (JMIR Publications, 2024)
BackgroundIschemic heart disease (IHD) is the leading cause of death among noncommunicable diseases worldwide, but data on current epidemiological patterns and associated risk factors are lacking. ObjectiveThis study assessed the global, regional, and national trends in IHD mortality and attributable risks since 1990. MethodsMortality data were obtained from the Global Burden of Disease 2019 Study. We used an age-period-cohort model to calculate longitudinal age curves (expected longitudinal age-specific rate), net drift (overall annual percentage change), and local drift (annual percentage change in each age group) from 15 to >95 years of age and estimate cohort and period effects between 1990 and 2019. Deaths from IHD attributable to each risk factor were estimated on the basis of risk exposure, relative risks, and theoretical minimum risk exposure level. ResultsIHD is the leading cause of death in noncommunicable disease-related mortality (118.1/598.8, 19.7%). However, the age-standardized mortality rate for IHD decreased by 30.8% (95% CI -34.83% to -27.17%) over the past 30 years, and its net drift ranged from -2.89% (95% CI -3.07% to -2.71%) in high sociodemographic index (SDI) region to -0.24% (95% CI -0.32% to -0.16%) in low-middle-SDI region. The greatest decrease in IHD mortality occurred in the Republic of Korea (high SDI) with net drift -6.06% (95% CI -6.23% to -5.88%), followed by 5 high-SDI nations (Denmark, Norway, Estonia, the Netherlands, and Ireland) and 2 high-middle-SDI nations (Israel and Bahrain) with net drift less than -5.00%. Globally, age groups of >60 years continued to have the largest proportion of IHD-related mortality, with slightly higher mortality in male than female group. For period and birth cohort effects, the trend of rate ratios for IHD mortality declined across successive period groups from 2000 to 2004 and birth cohort groups from 1985 to 2000, with noticeable improvements in high-SDI regions. In low-SDI regions, IHD mortality significantly declined in female group but fluctuated in male group across successive periods; sex differences were greater in those born after 1945 in middle- and low-middle-SDI regions and after 1970 in low-SDI regions. Metabolic risks were the leading cause of mortality from IHD worldwide in 2019. Moreover, smoking, particulate matter pollution, and dietary risks were also important risk factors, increasingly occurring at a younger age. Diets low in whole grains and legumes were prominent dietary risks in both male and female groups, and smoking and high-sodium diet mainly affect male group. ConclusionsIHD, a major concern, needs focused health care attention, especially for older male individuals and those in low-SDI regions. Metabolic risks should be prioritized for prevention, and behavioral and environmental risks should attract more attention to decrease IHD mortality.